(untitled) (Revista Lusófona de Educação, 2018)
Due to age discrimination, retirees are usually viewed as a homogeneous group and therefore are all treated in the same way by society. In-depth research into the differences between the individuals in this age group gives us the opportunity to discover if all retirees deal with this change in the same manner. The objective of our study is to identify different profiles in a sample of Spanish retirees enrolled in university programs according to different factors. 991 Spanish retirees were evaluated both in terms of continuous variables, such as organizational pressures, health problems, interest in retirement, levels of work-related stress, social support and resilience, and demographic variables. A cluster analysis was performed which enables the definition of groups with homogeneous characteristics within large samples. The variables were included in each of the clusters using Student’s t-test for the continuous variables and a chi squared test for the categorical variables. The results of the analysis confirm the existence of four groups or clusters based on the variables used in the research. The differentiation of profiles for retirees helps to eliminate social discrimination motived by age and mistaken beliefs about retirees (ageism) and assists in the adjustment and personalization of retirement preparation programs. Keywords: retirement; resilience; social support; satisfaction; cluster analysis.